A comparative study on intrinsic mobility of incoherent and semicoherent interfaces during the austenite to ferrite transformation. (November 2020) - Dong, Haokai; Zhang, Yongjie; Miyamoto, Goro; Chen, Hao; Yang, Zhigang; Furuhara, Tadashi
Abstract: A straightforward approach to experimentally determine intrinsic interface mobility as well as extrinsic energy dissipation is proposed based on the measurements of total energy dissipation and interface velocity. These parameters have been comparatively studied for incoherent allotriomorphic ferrite (AF) and semicoherent Widmanstätten ferrite (WF) in an Fe-C alloy. It reveals that extrinsic energy dissipation for AF is negligibly small whereas that for WF is about 20J/mol, which should correspond to the dissipation by associated transformation strain. Furthermore, the intrinsic mobility of the semicoherent WF/austenite interface is found to be much smaller than the incoherent AF/austenite interface counterpart. Graphical Abstracts: Image, graphical abstract